Osmoregulation pattern, condition factor, and gonadal maturity level of sea urchins in the various ecosystems of Panjang Island, Jepara, Indonesia - SURYANTI SURYANTI; SUTRISNO ANGGORO; CHURUN A’IN; NINIEK WIDYORINI (Society for Indonesian Biodiversity, 2024)
Abstract. Suryanti S, Anggoro S, A’in C, Widyorini N. 2024. Osmoregulation pattern, condition factor, and gonadal maturity level of sea urchins in the various ecosystems of Panjang Island, Jepara, Indonesia. Biodiversitas 25: 502-509. Panjang Island has a diversity of ecosystems. It is also famous for its abundance of echinoids, especially sea urchins. Currently, research on sea urchins in Panjang Island is mostly limited to studies on the abundance and maturity of gonads. This study investigates the osmoregulation patterns, condition factors, and maturity indices of sea urchin gonads in different ecosystems that are sea urchin habitats on Panjang Island, Jepara, Indonesia. Sampling is done randomly, while the research method is a case study. The results showed that there are 2 species of sea urchins found on Panjang Island, namely Diadema setosum Leske, 1778 and Echinothrix calamaris Pallas, 1774. Analysis of osmoregulation patterns showed that sea urchins at station 1 were hyperconformers, while sea urchins at stations 2 and 3 were hypo-conformers. Sea urchins at 3 stations had a positive allometric growth pattern (b>3) and a high condition factor (K>1). The average Gonadosomatic Index (GI) calculation result was 8.72%, while the type of ecosystem of the research stations influenced the color and texture of different gonads. Sea urchins are in immature, mature, and spawning stages, so the sea urchins on Panjang Island were partially spawned.